Lipid droplets in plants: turnover and stress responses - Zhao, Yujie; Cao, Rui; Li, Jincheng; Xu, Yingying; Zhou, Lijuan; Ye, Yajin (Frontiers in Plant Science, 2025)
Lipid droplets (LDs) have emerged as dynamic organelles central to plant lipid metabolism, stress adaptation, and energy homeostasis. This review synthesizes recent advances in understanding LD biogenesis and degradation in plants, highlighting conserved and divergent mechanisms relative to other eukaryotes. LD formation originates in the endoplasmic reticulum (ER), where neutral lipids synthesized by diacylglycerol acyltransferases (DGAT) and phospholipid: diacylglycerol acyltransferases (PDAT) accumulate into lens-like structures. These structures bud into the cytosol via ER machinery, including SEIPIN complexes, vesicle-associated membrane proteins, and LD-associated protein-interacting protein which regulate LD size and abundance. Degradation occurs through two major pathways: lipolysis, mainly mediated by the patatin-like lipase SUGAR-DEPENDENT1, and lipophagy, where AUTOPHAGY-RELATED proteins deliver LDs for breakdown. LDs also function as stress-responsive hubs, accumulating under abiotic stresses and during pathogen interactions, where they participate in membrane remodeling and antimicrobial defense. Extensive studies in major oilseed crops reveal that expressions of multiple genes involved in LD turnover are significantly induced under various abiotic stresses and phytohormone treatments. These genetic components operate autonomously or synergistically (e.g. DGAT and PDAT) within the TAG biosynthesis and LD metabolic pathways, effecting concurrent enhancements in stress resilience and oil production under suboptimal growth conditions. Critical knowledge gaps persist, including the interplay between lipolysis and lipophagy, the integration of energy-related signaling pathways in LD turnover, and stress-modulated post-translational control of LD proteome. Deciphering these mechanisms will advance our understanding towards LD biology.